Recurrent petit traumatic hernia plasty: case report - Estudillo, Gamaliel Vázquez; Ochoa Viveros, Edwin Y.; Nicasio Delgado, Amado Q.; Cervantes, David Trejo; Cajica, Gerardo Rodarte; Hernández Rojas, Manuel A.; Salazar, Ivanhoe Larracilla (International Surgery Journal, 2019)
Lumbar hernias are very infrequent posterior abdominal wall defects. They are usually located in the upper lumbar triangle and represent approximately 1.5-2% of all hernias of the abdominal wall. In fact, there are few cases described in the literature and most of the large hospital centers have published only 2 or 3 cases. This is a 34 year-old female, who suffered a car accident, in which bilateral femoral fracture and left humeral fracture, after recovery of said fractures has asymmetry of flanks with the appearance of volume increase in the left abdominal flank, computed tomography was performed evidencing left lower lumbar hernia (Petit’s Hernia) so, it was protocolized for open lumbar hernia repair with placement of mesh by anterior approach, later one year later, it presented recurrent left lumbar hernia, therefore, a protocol and surgical procedure of open lumbar plasty was performed again with mesh placement by lumbotomy approach in 2016. After a year of the surgical procedure, a pelvic abdominal control CT scan was requested, where a proper prosthesis placement was observed without protruding tissues. This was the first case of recurrent post-traumatic Pettit hernia in this institution. There are few cases reported in the universal literature, the treatment was surgical when performing the diagnosis, either laparoscopically or openly with decision and according to the experience of the surgeon.